Help-seeking behaviours for mental health in higher education. Issue 4 (21st April 2022) - Bryant, Ashleigh; Cook, Amy; Egan, Helen; Wood, Jeffrey; Mantzios, Michail
ABSTRACT: Researchers have studied help-seeking behaviours regarding students' mental health, highlighting their reluctance when in higher education. This study aimed to identify the facilitators and barriers to formal and informal sources of help-seeking for mental health difficulties in students based in the UK. Data from 304 participants (82% females) was explored using quantitative self-report methods. The results indicated that help-seeking behaviours were related with living arrangements, sexuality and age: Commuter students were more likely to seek help from their personal tutor compared to those living on campus. Students who identified as Lesbian, Gay, Bisexual, Queer, Questioning and Transitioning (LGBTQQ) were more likely to engage with off-campus services than non-LGBTQQ students and young people were more likely to seek informal support from family and friends compared to older students. In contrast, the findings show that student help-seeking behaviours were related with a sense of belonging and ethnicity: As students sense of belonging to their university increased, so did their help-seeking behaviour. Black, Asian or Minority Ethnic (BAME) students were more likely to engage with professional services from personal tutors and mental health services in comparison to White students, who were more likely to seek help from their peers. Findings highlighted the importance of creating effective programmes that encourage students to discuss mental health and improve help-seeking behaviours.